Analisis Kualitas Layanan Terhadap Penggunaan Aplikasi Blended Learning Menggunakan Model EESS - Tatumang, Elsia Miranda Mildad; Ahmatang, Ahmatang (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : This study aims to test the Quality of Moodle Borneo E-Learning (BEL) which includes Service Quality, Student Quality and Lecturer Quality on Perceived Satisfaction, Perceived Usefulness and Benefits based on the E-learning System Success Evaluating Model for active BEL users Design/Methode/Approach : This research uses a quantitative approach with non-probability sampling method and the technique used is Quota Sampling. To determine the number of samples, the hair formula was used which determined that the sample consisted of 280 University of Borneo students who had used BEL. The data analysis method used is SEM (Structural Equation Modeling) with the help of the SmartPLS program. Research Finding : The results showed that the variables of Service Quality, Student Quality and Lecturer Quality had a positive and significant effect on satisfaction and usability. And the Satisfaction and Usefulness Variables also have a positive and significant effect on benefits. Theoretical contribution/Originality : It is hoped that this research can provide insight and knowledge as well as provide information to researchers and academics regarding the analysis of the quality of BEL application service quality using the EESS model. Practitionel/Policy implication : The results of this study are used as input for the Borneo Tarakan University's LP3M, so that in the future it can improve the quality and quality of BEL so that in the future students will be more comfortable doing online learning with BEL. Research limitation : In this study it only focuses on evaluating the quality of using the BEL application but only looks at it from the perspective of students at the University of Borneo Tarakan. And also focuses on the EESS conceptual model which includes only social factors, namely Service Quality, Learner Quality, Instructor Quality. sitive and significant effect on benefits